2011
DOI: 10.1007/s10903-011-9491-4
|View full text |Cite
|
Sign up to set email alerts
|

Chinese-Australian Women’s Knowledge, Facilitators and Barriers Related to Cervical Cancer Screening: A Qualitative Study

Abstract: Understanding the different facilitators and barriers to screening within cultural and ethnic groups is important for developing appropriate education and outreach programs to underserved groups. Qualitative methods were employed to gain a rich understanding of participant views. In-depth interviews were conducted with 18 Chinese Australian women in their native languages and analysed using content analysis. Knowledge of cervical cancer was low, and few participants understood the benefits and purpose of scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
83
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 53 publications
18
83
0
3
Order By: Relevance
“…For instance, modesty, embarrassment and the need to show breasts to doctors especially mal doctors for screening are negative effects on a woman's decision making to participate in breast cancer screening. This is consistent with previous study; reported that physicians' gender can affect whether women decide performing screening behavior, such as Pap tests, mammography and clinical breast examination or not (Banning, 2009;Kwok, 2011;Taha, 2012;Kwon, 2013).…”
Section: 3965 Perception Of Breast Cancer Screening Among Iranian Wosupporting
confidence: 92%
“…For instance, modesty, embarrassment and the need to show breasts to doctors especially mal doctors for screening are negative effects on a woman's decision making to participate in breast cancer screening. This is consistent with previous study; reported that physicians' gender can affect whether women decide performing screening behavior, such as Pap tests, mammography and clinical breast examination or not (Banning, 2009;Kwok, 2011;Taha, 2012;Kwon, 2013).…”
Section: 3965 Perception Of Breast Cancer Screening Among Iranian Wosupporting
confidence: 92%
“…33,42 Others had applied interviews or self-report questionnaires to study participants' knowledge, and attitude towards and participation in health care services. [30][31][32]35,37,40 Participation in community and social occupations was mostly identified through questionnaires or interviews, in either self-reported data or narratives that were later interpreted in these studies. 29,37,38,40,43 It seems there was no consensus in either the definition or the way the concept of participation was approached and measured within the context of immigration studies.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Family attitudes and support were also important. 33,34 For women in particular, their spouses' attitudes or permission were important factors, which may help or hinder participation.…”
Section: Sub-theme 2a Enabling Facilitating Encouraging Supportinmentioning
confidence: 99%
See 2 more Smart Citations